Einige Erwägungen über die Beziehungen zwischen den Begriffen ’Synanthrop’ und ’Kulturfolger’. - Povolný, Dalibor (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There is made an attempt to show that there are some significant differences between synanthropes and the so-called „Kulturfolger". While synanthropy means a zoocoenologic category (i.e. a spontaneous membership of the anthropobiocoenosis), the „Kultur-folger" are mainly „paröke Formen" in relation to mankind. This character, however, belongs into the field of animal ethology and not into that of chorology or biocoenology.